2020
DOI: 10.1177/2056305120924771
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Expression of #body on Instagram

Abstract: Our aim was to explore emotions in Instagram images marked with hashtags referring to body image–related components using an artificial intelligence–based discrete emotional analysis. A total of 500 Instagram photos marked by specific hashtags related to body image components were analyzed and specific discrete emotions expressed in each picture were detected using the Emotion application program interface API from Microsoft Azure Cognitive Service. Results showed that happiness and neutrality were the most in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 65 publications
0
12
0
1
Order By: Relevance
“…Therefore, the present cross-cultural validation study may allow capturing both core emotional themes, and their variations also related to other phenomena, in this case, personality traits. This result maybe relevant also in the clinical field, since it could help clinicians design tailored interventions for people suffering from personality or affective disorders, in relation to the emotion regulation strategies they usually adopt to manage positive emotions [e.g., 84 , 85 ]. In brief, the Italian DPES is easy to administer and can provide quick information on frequently experienced emotions and their link with other emotional or cognitive processes across a wide array of domains.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the present cross-cultural validation study may allow capturing both core emotional themes, and their variations also related to other phenomena, in this case, personality traits. This result maybe relevant also in the clinical field, since it could help clinicians design tailored interventions for people suffering from personality or affective disorders, in relation to the emotion regulation strategies they usually adopt to manage positive emotions [e.g., 84 , 85 ]. In brief, the Italian DPES is easy to administer and can provide quick information on frequently experienced emotions and their link with other emotional or cognitive processes across a wide array of domains.…”
Section: Discussionmentioning
confidence: 99%
“…The egocentric parietal representations shape the short-term memory of perceptual information, while the medial temporal allocentric representations sustain the long-term memory (Byrne et al, 2007;Chirico et al, 2019;Cipolletta et al, 2017;Malighetti et al, 2016Malighetti et al, , 2019Malighetti et al, , 2020Matamala-Gomez et al, 2020;Serino et al, 2015Serino et al, , 2016Tuena et al, 2021). Accordingly, these frames are supposed to play a critical role in the way memories are stored and retrieved (Akhtar et al, 2017;Byrne et al, 2007).…”
Section: Correcting Multisensory Integration Deficits In Ed: the Reference Frame Shifting Approachmentioning
confidence: 99%
“…Instagram facilitate informative visuals that lead to emotional appeal that can influence customer engagement in terms of likes and comments, so that Instagram is very suitable as a marketing media for advertising [60] as well as Facebook [61] with the difference that Instagram is more to emotional expression with real experiences while Facebook is more to wide user without likely used by youngster. However, even though Twitter has a similarity as social media with Instagram, this social media is more to conversation, and the interview result showed that Twitter was not suitable to market a product [62][63] [64][65] [66].…”
Section: Customer Can Comment and Respond To Our Posting Of Activities Thus Creates Bonding With Us I Like To Use These Two To Market Thementioning
confidence: 99%